Determination of nine volatile N‐nitrosamines in tobacco and smokeless tobacco products by dispersive solid‐phase extraction with gas chromatography and tandem mass spectrometry. Issue 11 (28th April 2016) - Lv, Fang; Guo, Junwei; Yu, Fei; Zhang, Tingting; Zhang, Shimin; Cui, Huapeng; Liu, Xianjun; Chen, Li; Liu, Leiyu; Liu, Shaofeng; Xie, Fuwei
Abstract : A method was developed for the determination of nine volatile N‐nitrosamines in tobacco and smokeless tobacco products. The targets are N ‐nitrosodimethylamine, N ‐nitrosopyrrolidine, N ‐nitrosopiperidine, N ‐nitrosomorpholine, N ‐nitrosoethylmethylamine, N ‐nitrosodiethylamine, N ‐nitrosodipropylamine, N ‐nitrosobuylmethylmine, and N ‐nitrosodibutylamine. The samples were treated by dispersive solid‐phase extraction using 1 g of primary secondary amine and 0.5 g of carbon and then analyzed by gas chromatography with tandem mass spectrometry with an electron impact ion source. The recoveries for the targets ranged from 84 to 118%, with <16% relative standard deviations at three spiking levels of 0.5, 1.25, and 2.5 ng/g. The limits of detection ranged from 0.03 to 0.15 ng/g. With the use of the proposed method, we detected the presence of six nitrosamines in the range of 0.4–30.7 ng/g. The study demonstrated that the method could be used as a rapid, convenient, and high‐throughput method for N‐nitrosamines analysis in tobacco matrix.